Pseudo-Maṣlaḥah and Epistemological Failure in Marriage Dispensation at Indonesian Religious Courts - Azni, Azni; Hafis, Muhammad; Zakariah, Asril Amirul; Harmanto, Adi; Miftahuddin, Miftahuddin; Ihsan, M. (SCAD Independent, 2025)
This study looked at how maṣlaḥah (public interest) was used in marriage cases in the Religious Courts of Sumatra, Indonesia, and how it was related to the goals of maqāṣid al-sharī’ah. Based on a qualitative analysis of 48 court decisions and in-depth interviews with six judges, the research revealed that the concept of maṣlaḥah was often employed as a procedural justification to accommodate social pressure, rather than as an evaluative ethical-legal framework. Judges tended to prioritize the protection of religion (ḥifẓ al-dīn)—mainly by preventing adultery—while neglecting essential dimensions such as protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-’aql), and progeny (ḥifẓ al-nasl). This reductionist approach leaded to the legitimization of underage marriage without proper psychological, biological, or economic assessments. The study found that such practices contributed to systemic harm, including early divorce, reproductive health risks, and intergenerational poverty. By critically examining the misuse of maṣlaḥah, this research offered an epistemological critique and proposes a reconstructive framework grounded in empirical evaluation and child-centered justice. It concluded that the reform of Islamic family law requires not only regulatory improvement but also a transformation of judicial reasoning. This study contributes to broader discussions on Islamic legal reform and child protection in Muslim-majority contexts.